2002
DOI: 10.1007/s00221-001-0994-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of brain activity during different types of proprioceptive inputs: a positron emission tomography study

Abstract: It has been shown that the primary and secondary somatosensory cortex, as well as the supplementary motor area (SMA), are involved in central processing of proprioceptive signals during passive and active arm movements. However, it is not clear whether different cortical areas are involved in processing of different proprioceptive inputs (skin, joint, muscle receptors), what their relative contributions might be, where kinesthetic sensations are formed within the CNS, and how they interact when the full periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
77
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(92 citation statements)
references
References 41 publications
11
77
1
Order By: Relevance
“…Among other functions, the SMA seems to be involved in movement control ( [Cunnington et al, 2002], [Floyer-Lea and Matthews, 2004], [Stephan et al, 1995] and [Vaillancourt et al, 2003]) which would support the idea of ERS reflecting a reset of cortical activity in brain regions involved in a motor task as expressed in the 'idling' hypothesis . On the other hand, the SMA receives proprioceptive input from sensory afferents stimulated by passive movements (Radovanovic et al, 2002), supporting the reafferent input hypothesis of ERS ( [Cassim et al, 2001] and [Labyt et al, 2003]). Another medial frontal structure, the anterior cingulate cortex (ACC), has been suggested to have a fundamental role in relating actions to their consequences (Rushworth et al, 2004).…”
Section: Post-movementsupporting
confidence: 60%
“…Among other functions, the SMA seems to be involved in movement control ( [Cunnington et al, 2002], [Floyer-Lea and Matthews, 2004], [Stephan et al, 1995] and [Vaillancourt et al, 2003]) which would support the idea of ERS reflecting a reset of cortical activity in brain regions involved in a motor task as expressed in the 'idling' hypothesis . On the other hand, the SMA receives proprioceptive input from sensory afferents stimulated by passive movements (Radovanovic et al, 2002), supporting the reafferent input hypothesis of ERS ( [Cassim et al, 2001] and [Labyt et al, 2003]). Another medial frontal structure, the anterior cingulate cortex (ACC), has been suggested to have a fundamental role in relating actions to their consequences (Rushworth et al, 2004).…”
Section: Post-movementsupporting
confidence: 60%
“…Studies of cortical activity during finger flexion have reported no activity in the insula (14) using combined fMRI and electromyography. Similarly, positron emission tomographic (PET) studies during arm flexion have not reported changes in blood flow in the insular cortex (38). Illusionary arm flexion/extension has been reported to be associated with insular activity (32).…”
Section: Discussionmentioning
confidence: 99%
“…15,25,26 At a slightly lower threshold of P ≤ 0.1 (FWE) revealed a contralateral cluster of activation in S1 further supporting the stimulation of the sensorimotor network by the kinesthetic illusion. Although our protocol of continuous stimulation was unusual the stimulus changed regularly between the high illusion inducing frequencies and the low sensory frequencies so the muscle spindles endings were not constantly producing movement signals.…”
Section: Discussionmentioning
confidence: 99%